Validation of the Hebrew version of the Burn Specific Health Scale-Brief questionnaire. Issue 1 (February 2015) - Stavrou, Demetris; Haik, Josef; Wiser, Itay; Winkler, Eyal; Liran, Alon; Holloway, Samantha; Boyd, Julie; Zilinsky, Isaac; Weissman, Oren
Abstract Background The Burns Specific Health Scale-Brief (BSHS-B) questionnaire is a suitable measurement tool for the assessment of general, physical, mental, and social health aspects of the burn survivor. Aim To translate, culturally adapt and validate the BSHS-B to Hebrew (BSHS-H), and to investigate its psychometric properties. Methods Eighty-six Hebrew speaking burn survivors filled out the BSHS-B and SF-36 questionnaires. Ten of them (11.63%) completed a retest. The psychometric properties of the scale were evaluated. Internal consistency, criterion validity, and construct validity were assessed using interclass correlation coefficient, Cronbach's alpha statistic, Spearman rank test, and Mann–Whitney U test respectively. Results BSHS-H Cronbach's alpha coefficient was 0.97. Test–retest interclass coefficients were between 0.81 and 0.98. BSHS-H was able to discriminate between facial burns, hand burns and burns >10% body surface area (p < 0.05). BSHS-H and SF-36 were positively correlated (r2 = 0.667, p < 0.01). Conclusions BSHS-H is a reliable and valid instrument for use in the Israeli burn survivor population. The translation and cross-cultural adaptation of this disease specific scale allows future comparative international studies.